Dinamika Interaksi Sosial Masyarakat Kampung Marikla - Tengget, Lukas (JURNAL EKOLOGI BIROKRASI, 2023)
This article aims to analyze the patterns and forms of social interaction in Marikla Village, Pamek District, Bintang Mountains Regency, factors as well as barriers and drivers of social interaction patterns. The research method is descriptive qualitative. The data collection techniques used were observation, in-depth interviews and documentation. The informant selection technique was purposive by involving 10 informants in the research. The data analysis method used includes stages of data reduction, data presentation, and inference. The research results show that the pattern of social interaction in community life includes religious activities, socio-cultural activities and mutual cooperation. Forms of social interaction in community life that occur between individuals or people and groups have a reciprocal relationship and can be created through contact and communication, which gives rise to various social interactions, mainly based on the interests and degree of group interaction. Factors that influence social interaction patterns in community life, the existence of kinship system attitudes and community cultural values.